1976
DOI: 10.1111/j.1533-8525.1976.tb01715.x
|View full text |Cite
|
Sign up to set email alerts
|

State of the Field The Conceptualization of Scientific Specialties

Abstract: This paper analyzes the phenomenon of research specialization in science. The format consists of two sections. The first features a state-of-the-art review of evidence from so-called specialty case studies on definitions, measurement strategies, and representations of the relations in which small groups of researchers cohere. In the second section, a theoretical perspective on the development of specialties is formulated. This perspective incorporates demographic factors into the study of specialty structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(103 citation statements)
references
References 71 publications
3
97
0
3
Order By: Relevance
“…Recently, as described in Howe (2008: p.150 (Mullins 1972), and protein crystallography (Law 1973) found that scientists responsible for major innovations in a field tended to be marginal to that field (Chubin 1976). However, marginality need not be responsible for big scientific breakthroughs only; it can also operate within disciplines and be helpful in solving micro-issues and "smaller" problems (Dogan and Pahre 1990).…”
Section: Section 3 the Advantage Of Marginalitymentioning
confidence: 99%
“…Recently, as described in Howe (2008: p.150 (Mullins 1972), and protein crystallography (Law 1973) found that scientists responsible for major innovations in a field tended to be marginal to that field (Chubin 1976). However, marginality need not be responsible for big scientific breakthroughs only; it can also operate within disciplines and be helpful in solving micro-issues and "smaller" problems (Dogan and Pahre 1990).…”
Section: Section 3 the Advantage Of Marginalitymentioning
confidence: 99%
“…Our algorithm unambiguously reveals that, in terms of the hierarchy of different community sizes, specialties are the smallest subset of authors that can be "brought together". These techniques could be of great use to historians or sociologists of science, by tracking the emergence, demise, proximity or fusion of specializations, as well as the evolution of scientific paradigms (Mullins, 1972;Chubin, 1976;Mullins et al, 1977;Small, 2006). Given a specific community, we can identify -using keywords, for instance -its ideas, methods and membership.…”
Section: Resultsmentioning
confidence: 99%
“…The first bibliometricians tended to use counts of citations as an indication of the directions in which science was moving. However, according to Chubin (1976Chubin ( , 1981, limitations associated with measuring and scaling these outputs soon went beyond simply counting of citations to more complicated statistical and mathematical techniques that would allow bibliometricians to describe, in quantitative terms, the structure of the information base reflected in the scientific literature. Now that these tools have been developed, bibliometricians are attempting to use them to evaluate research projects and programs on an ex post basis.…”
Section: Biblwmetric Methodsmentioning
confidence: 99%